The physiological restorative effects in changing air temperature among various landscape composition of green spaces during summer: Empirical evidence from Chongqing, China - Jingeng Huo; Hongqiao Qin; Dan Hong; Jiaqi Niu; Haoyan Wu; Xuelin Wei; Guifeng Han; Jie Yan; Zhiyong Liu (Ecological Indicators)
As vital infrastructures, green spaces provide important places for outdoor activities and social interactions for urban residents. Previous studies have shown that visiting green spaces significantly enhances physiological restorative effect (PRE) on human health. However, when exposed to outdoor environments in hot summer, are there significant differences in various landscape effects and PRE among various green spaces as air temperature (Ta) increases? This study quantified PRE by measuring heart rate, blood oxygen, systolic and diastolic blood pressure in three types of green spaces selected in Chongqing during summer. Mixed effects and hierarchical multiple regression were analyzed for 13 landscape indicators and PRE under 2 °C changes in Ta. The results showed that PRE diminished overall as Ta increased. A robust PRE was observed at 26–32 °C, and recovery abilities of four physiological health indicators began to decrease when Ta exceeded 32 °C. The impacts of landscape indicators on PRE were significantly adjusted by Ta, with under branch height and number of plant species being important driving forces. Based on these findings, a PRE calendar was developed, suggesting that square spaces are suitable for visit during the morning and evening, while tree-covered and waterfront spaces are preferable at other times. These findings can provide valuable insights for urban planners to improve the design and management of green spaces, thereby guiding visitors’ activity behavior and site selection to enhance overall comfort when visiting green spaces.